Tinjauan Histori pada Gaya Visual Iklan Cetak Coca-Cola - Nadia Sigi Prameswari (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2020)
Zeitgeis (the soul of the times) has a great influence on the characteristics of works of art in the form of paintings, sculptures, reliefs, illustrations, writing to develop into advertisements. Advertising is one of the works of art that appeared in the 17th century. In the 1880s, several manufacturers or companies adapted the techniques by which advertisements appeared on posters. Various producers of food, beverage, medicine and toiletries began to introduce their products through poster advertisements. In 1886, The Coca-Cola Company was founded in America. In 1906, William D'Arcy joined as the Creative Team that planned the Coke advertising concept and had the view that "Coca-Cola commercials should create scenes that draw people in and make them part of a pleasant interlude of everyday life." This study is a historical review of the influence of styles during the Antiquity, Mediaeval, Renaissance, and Baroque periods on the development of the visual style of Coca-Cola's print ad. Zeitgeis provided a transition to the development of the visual style of Coca-Cola's print advertising in every period of time.